MUSIC AND POLITICS: 80S ROCK AND REPRESENTATIONS OF BRAZILIAN SOCIETY - Fabrício, Lívia Badaró (2023)
This paper focuses on two songs rock bands that emerged in Brazil in the 1980s and aims to understand the peculiarities of this generation, as well as the socio-political and cultural era.